2021
DOI: 10.3390/app11177788
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic and Antioxidant Activities of Flavonoid-Rich Extract of Ziziphus lotus (L.) Lam. Fruits

Abstract: Ziziphus lotus (L.) Lam. (Z. lotus) is a medicinal plant species that is widely distributed throughout the Mediterranean basin. Moroccans traditionally use it to treat many illnesses thanks to its beneficial medicinal properties. The purpose of this study is to assess the anti-hyperlipidemic and antioxidant activities of a flavonoid-rich aqueous extract of Z. lotus fruits (ZLF). The 2-2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay and the β-carotene bleaching test were used to determine the antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…Plants have always played a significant role in traditional medicine in underdeveloped countries and have also been an integral part of local communities' history and cultural practices [1]. Medicinal plants have been recognized for centuries as a rich source of medicinal agents for preventing and treating a variety of ailments in Morocco [2]. Several researches conducted in different regions of Morocco indicated that people excessively use medicinal plants to meet their healthcare needs in Morocco (at least 75% of the population) [3,4] and it is due to several factors, such as the high cost of conventional medicines, the lack of adequate sanitary facilities, and frangible socioeconomic conditions of users, especially those living in poor, remote areas and also their safety and low incidence of adverse effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Plants have always played a significant role in traditional medicine in underdeveloped countries and have also been an integral part of local communities' history and cultural practices [1]. Medicinal plants have been recognized for centuries as a rich source of medicinal agents for preventing and treating a variety of ailments in Morocco [2]. Several researches conducted in different regions of Morocco indicated that people excessively use medicinal plants to meet their healthcare needs in Morocco (at least 75% of the population) [3,4] and it is due to several factors, such as the high cost of conventional medicines, the lack of adequate sanitary facilities, and frangible socioeconomic conditions of users, especially those living in poor, remote areas and also their safety and low incidence of adverse effects [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tey were also higher than those reviewed by Abdoul-Azize [6] (1.22 mg/g DM). TFC values from water extracts were higher than those obtained by Dahlia et al (0.83 ± 0.09-0.98 ± 0.01 mg QE/g DM) [48] and Bencheikh et al (2242.89 ± 25 μg QE/mg DM) [51]. According to outcomes, TFC of Z. lotus fruits was signifcantly infuenced by the geographical origin as well as the solvent used.…”
Section: Discussionmentioning
confidence: 57%
“…Flavonoid compounds are associated with a number of biological activities, their antioxidant, anticancer, anti-inflammatory, antidiabetic, antimicrobial, antidyslipidemic, neuroprotective, antiosteoporotic, cytoprotective, hepatoprotective, vasoprotective properties being much studied [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. Flavonoids are known to decrease cardiovascular risk and cancer-associated mortality [ 76 ].…”
Section: Flavonoidsmentioning
confidence: 99%